Assessment of three-dimensional biofilm structure using an optical microscope - Carla C.C.R. de Carvalho; M. Manuela R. da Fonseca (BioTechniques)
A method allowing the evaluation of the structure and the calculation of the volume of a biofilm, using an optical microscope, is proposed based on the linear relation between the intensity of a pixel in biofilm images grabbed on the x-y plane and the corresponding number of cells in the z direction, which allows the calculation of the biofilm thickness. The method is intended to overcome the need for expensive microscopes to study biofilms.